Optimalisasi Pembelajaran Tahfizh Al-Qur’an Berbasis Fungsi Otak - Maftukhah Maftukhah; Rahmat Hariyadi (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
This article related to the idea of optimizing learning tahfizh Al-Qur'an based on brain function. The brain is a complex part of the human body and is always developing. Therefore, in the process of learning Al-Qur'an tahfizh, we must consider the work and function of each component of the human brain: first, the reptile brain which functions to regulate the heart, lungs, and respiratory system. Second, the limbic brain which functions to regulate the immune system, family needs, social stratification, a sense of belonging, emotional nature, and hormones. Third, the neo-cortex or big brain functions to think, organize logic, respond to things rationally, and master the world's creativity. The purpose of writing this article is to provide an overview of creative and innovative Al-Qur'an tahfizh learning planning by optimizing brain function. This research is included in qualitative research using library research methods. With this research, we can see that in the process of learning tahfizh Al-Qur'an which is creative and innovative in formal and non-formal educational institutions, we can optimize it by utilizing the functions of the human brain that are in accordance with brain waves. Human brain waves consist of gamma waves, beta waves, alpha waves, theta waves, delta waves. When a learner in the process of learning Al-Qur'an tahfizh can enter the alpha wave, it will be easier to carry out the process of memorizing the Al-Qur'an.